The express-diagnostics of versions of a DIC-syndrome in trauma and acute haemorrhage patients - Ye. G. Ripp; V. Ye. Shipakov; M. N. Shpisman (Бюллетень сибирской медицины)
The research of a haemostatic system in trauma and acute haemorrhage patients by a new instrumental method — haemocoagulographia — allows at early stages of disease to reveal patients having the tendency to development haemostatic anomalies, Multi Organ Dysfunction Syndrome and failure of disease, that increases accuracy of an evaluation of weight of a condition and prognosis on APACHE-III system (Acute Physiology And Chronic Health Evaluation).